Multisensor Data Fusion and Integration for Mobile Robots: A Review - KS Nagla; Moin Uddin; Dilbag Singh (Institute of Advanced Engineering and Science, 2014)
One of the most important and useful feature of autonomous mobile robots is their ability to adopt themselves to operate in unstructured environment. Today robots are performing autonomously in industrial floor, office environments, as well as in crowded public places where the robots need to maintain their localization and mapping parameters.The basic requirement of an intelligent mobile robot is to develop and maintain localization and mapping parameters to complete the complex missions. In such situations, several difficulties arise in due to the inaccuracies and uncertainties in sensor measurements. Various techniques are there to handle such noises where the multisensor data fusion is not the exceptional one.From the last two decades, multisensor data fusions in mobile robots become a dominant paradigm due to its potential advantages like reduction in uncertainty, increase in accuracy and reliability and reduction of cost.This paper presents the reviews of autonomous mobile robots and role of multisenosr data fusion.